Development of an Inquiry-Based Worksheet to Practice Cognitive and Science Process on Light Wave Concepts - Firdaus, Ikmal Sofil; Efendi, Ridwan; Sinaga, Parlindungan (Department of Physics Education, Universitas Mataram, 2025)
This study aims to develop inquiry skills science worksheets to practice cognitive abilities and science process skills. The research used R&D with ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants of this research consisted of lecturers, teachers, and students. The research sample consisted of two XI classes as experimental and control classes. The feasibility of the worksheet was analyzed by content validity index (CVI), the improvement of cognitive abilities and science process skills was analyzed using N-Gain, the effectiveness of the worksheet to practice cognitive abilities and science process skills was analyzed using cohen'd effect size, and student responses were analyzed using descriptive quantitative. The overall feasibility of the science inquiry skills worksheet was declared